From conception to consumption : an examination of the intellectual process of producing textbooks for Foundation Phase in South Africa. - Koornhof, Hannchen (My University, 2012)
This study examines the factors that shape decision-making in relation to the development of Learner Teacher Support Materials (LTSMs) in South Africa by focusing on the processes that govern the development of Foundation Phase LTSMs, and on how publishers understand the educational nature of LTSMs that will lead to effective literacy acquisition. Findings are based on elite interviews with members of senior management in the publishing industry, and triangulated with interviews with authors and academic specialists of Foundation Phase. It was found that the close alignment between government directives and processes and the publishing industry form the core of all LTSM development and production, creating some symbiosis as well as restraints. Factors that shape the production of LTSMs include full compliance with the specific outcomes of the curriculum; producing LTSMs that are affordable in terms of set criteria by selection committees; selection committees that, determine acceptance of LTSMs for placement on approved lists; time frames that preclude in-depth research and trialling, a market that is deeply stratified and where this stratification is reinforced by curriculum imperatives relating to language; and the monitoring of classroom productivity through the filling in of Learner Book worksheets. Best practice strategies for literacy acquisition requires materials considerably beyond what the industry is producing for South Africa’s most disadvantaged markets, namely the English First Additional Language market. Teacher training done by both publishers and the Department of Basic Education suggest a different conceptualisation of Teachers’ Guides are required in order for professional development to take place through LTSMs.
Keywords: Textbook publishing; Learner Teacher Support Materials; Foundation Phase; Literacy acquisition; English First Additional Language; Teachers' Guides